Quality Maintenance Effort Optimization in Software Industry - Nandi, Suvra (International Journal of Computer Sciences and Engineering, 2025)
This paper conceptualizes a very important Software Process metric Cost of Quality (COQ) in different aspects and provides ways to optimize its value through prior activity planning and implementing the tasks according to the pre-planned effort distribution. The solution is built based on the analogy between effort and real life cost expenditure. While the solution is direct, it deals with multiple pre-requisites like understanding the components of COQ, setting its limits which ensures both quality and budget. There are multiple important sub concepts coming out of it like Systematic Planning, Wastage Elimination, Prioritization of Tasks, and Modulated Effort leading to generation of regulated COQ value as Output. This article showcases the Pilot Results as experienced from few real life projects from one organization and simulated the real life scenario through step by step utilization of the proposed solution. The result shows that proposed solution is able to reduce variance by approx. 99% while achieving the sigma level improvement of approx. 3σ. The solution also ensures many potential benefits in many aspects like identifying gaps / quality vulnerabilities based on previous performances, prioritization of task, maintenance of balance between Cost & Quality, controlled utilization of available resources, waste identification, quantification & elimination.